The Microeconomics of Cryptocurrencies - Halaburda, Hanna; Haeringer, Guillaume; Gans, Joshua; Gandal, Neil (Journal of Economic Literature, 2022)
Since its launch in 2009 much has been written about Bitcoin, cryptocurrencies, and blockchains. While the discussions initially took place mostly on blogs and other popular media, we now are witnessing the emergence of a growing body of rigorous academic research on these topics. By the nature of the phenomenon analyzed, this research spans many academic disciplines including macroeconomics, law and economics, and computer science. This survey focuses on the microeconomics of crypto-currencies themselves. What drives their supply, demand, trading price, and competition amongst them? This literature has been emerging over the past decade and the purpose of this paper is to summarize its main findings so as to establish a base upon which future research can be conducted. (JEL D82, E42, G12)